Evolution of underground coal mine explosion law in Australia, 1887-2007 - Ghosh, Apurna; Wang, Sentai (Australian Mining History Association, 2014)
Underground coalmining is a notorious industry due to its poor safety record. During the early 20th century, the Australian underground coal mining industry was suffering from unacceptably high annual death rate. Today, Australian mining industry has developed safe working practices, rules and regulations and provides a safer working environment for miners. However, accidents and fatalities still occur and threaten the health and life of miners. Explosive atmosphere management is critical to ensure the safety of personnel and the mine itself. In order to achieve the final goal of zero harm, this research attempts to investigate the pattern of safety improvement by reviewing the Australian underground coal mine history. A time period from 1887-2007 is considered. Explosion control has some revolutionary improvements in both reducing the number of fatalities and fatality rates. The analysis of data has shown that mine explosions contributed to 74.58% of fatal injuries during 1887-1946; whereas, roof/side fall and machinery related accidents are contributing to 71% fatal injuries during 1947-2007. Over a century, a sophisticated legalisation system was built resulting in a dramatic improvement of underground coal mine explosion control performance. Several important revisions and amendments were made throughout this long period of progress. Roof falls and machinery gradually became the greater issue than explosions. As the continued amendment of existing regulation, the focus of the future legalisation will move on to specific regulations to specific mines according to different geological conditions, mining method and other varieties of aspects.